Caveability evaluation of block caving and prediction of caving fragmentation for a gold mine - Youtong, J.; Lianku, X.; Zhonghao, L.; Hui, C.; Guang, Z.; Aiai, W.; Shengqing, O.; Peng, L. (Caving 2026: Proceedings of the Sixth International Conference on Block and Sublevel Caving, 2026)
Block caving is a mining approach characterised by large production scale, low mining costs, and high production efficiency, making it one of the important choices for large-scale underground mine exploitation in China. This paper focuses on the block caving mining plan selected in the open pit to underground transition production planning design of a gold mine. By comprehensively utilising methods such as machine learning, big data analysis, 3D modelling, and numerical analysis, a systematic study on the caveability and caving fragmentation characteristics of ore and rock in the deep area of the mining area is conducted. For the basic information required in the mining rock mass rating (MRMR) evaluation system, detailed core engineering geological logging and investigation analysis of structural surfaces in open pit slopes are carried out. The Knearest neighbours algorithm is introduced to enhance the reliability of predicting engineering geological information in unknown areas, and then 3D modelling software is used to construct a 3D digital characterisation model of the engineering geological features of ore and rock based on multiple evaluation index systems, achieving refined classification evaluation of the caveability in the disturbed area. By comprehensively utilising the caving diagram method and caving fragmentation prediction analysis software, the prediction analysis of caving area and caving fragmentation is conducted, and combined with the mining design plan, the 3D numerical analysis method is used to simulate and study the caving characteristics of surrounding rock during the caving process of the mine, verifying the rationality of the caveability evaluation results. The research results show that the average MRMR of ore and rock within the 840 m to surface range of this gold mine is 54, with a caveability grade of class III moderate caving. The initial caving area of the eastern mine section is approximately 5,000 m², and the initial caving area of the western mine section is approximately 3,000 m². The predicted caving fragmentation of this gold mine is an average of 0.34–1.22 m³. The related results can provide a basic basis for the block caving mining design, optimisation of the bottom structure, and safe production of the mine.